2004
DOI: 10.1172/jci200421064
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct–specific knockout of endothelin-1 causes hypertension and sodium retention

Abstract: In vitro studies suggest that collecting duct-derived (CD-derived) endothelin-1 (ET-1) can regulate renal Na reabsorption; however, the physiologic role of CD-derived ET-1 is unknown. Consequently, the physiologic effect of selective disruption of the ET-1 gene in the CD of mice was determined. Mice heterozygous for aquaporin2 promoter Cre recombinase and homozygous for loxP-flanked exon 2 of the ET-1 gene (called CD-specific KO of ET-1 [CD ET-1 KO] mice) were generated. These animals had no CD ET-1 mRNA and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(166 citation statements)
references
References 52 publications
(32 reference statements)
6
158
1
Order By: Relevance
“…A role for renal medullary derived ET-1 in the control of renal excretory function has accumulated over recent years (1,8,21). Multiple studies indicate the importance of this system becomes greater as Na ϩ intake is increased (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for renal medullary derived ET-1 in the control of renal excretory function has accumulated over recent years (1,8,21). Multiple studies indicate the importance of this system becomes greater as Na ϩ intake is increased (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pollock and others (4)have shown that renal ET-1 production is enhanced in response to 1 wk of a high-sodium diet, and intramedullary blockade of ET B receptors for 7 days leads to salt-sensitive hypertension. In addition, specific knockout of the ET B receptor gene and the ET-1 gene in the medullary collecting duct produces salt-sensitive hypertension (1,6).…”
mentioning
confidence: 99%
“…New technology that allows deletion or expression of a particular gene in specific tissues in the kidney is an important scientific advance. Over the past few years, various animal models have been developed using such technology 13,[93][94][95] that provide new means of studying the physiological actions of a single NOS isoform in a single cell type at a specific point in time in vivo.…”
Section: Perspectivesmentioning
confidence: 99%
“…185 Moreover, it was shown that altered ET-1 production may contribute to hypertension. 186,187 Several human studies demonstrated a correlation between plasma or urinary levels of ET-1 and markers of DN, such as hyperfiltration, mesangial expansion, macro-and/or microalbuminuria, and uremia. [188][189][190][191][192] In addition, interventional studies using endothelin-receptor-blockers have yielded encouraging results [193][194][195][196][197][198] in rodent models of DMT1 195,198 or DMT2.…”
Section: Endothelin (Et) Blockersmentioning
confidence: 99%